POWTOON POP UP BOOK DIGITAL UNTUK MENINGKATKAN HASIL BELAJAR PPKN SISWA KELAS 5 SD UPT SD NEGERI 101740 TANJUNG SELAMAT - Dwi Priyanti; Gabriela Anjelika Br. Sebayang; Ficha Aulia Nanda (LPPM Universitas Cipta Mandiri, 2025)
This research is motivated by the limited use of learning media, and there are students who are not motivated in learning, one of which is on the material Pancasila in my life. The objectives of this study are: (1) to describe the process of developing the Powtoon Pop Up Book Digital learning media on the material of the form of objects and their changes. (2) to analyze the response of teachers in grade V to the practicality of the Powtoon Pop Up Book Digital learning media on the material of the form of objects and their changes. (3) to analyze the effectiveness of the Powtoon Pop Up Book Digital learning media on the learning outcomes of grade V students of SD 101740 Tanjung Selamat. The research method used is Research and Development (R&D), using the ADDIE model. The results of the study showed that the Powtoon Pop Up Book Digital learning media on the material Pancasila in my life had met the